Classifying Uruguayan maize collection to develop a core collection - Malosetti, M.; Abadie, T. (Agrociencia Uruguay, 2022)
Core Collections were suggested to improve germplasm utilization. A Core Collection is a subset of reduced size, chosen to represent the diversity of a collection with a minimum of redundancies. Because diversity is distributed between and within groups with different degrees of organization, accessions should be classified adequately into related groups before the selection of a Core Collection. In this research, different classification strategies for the Uruguayan Maize Collection were compared, and the best was used to select a Core Collection. The following classification strategies were compared following a multivariate approach using the available maize data base: i) racial classification, ii) geographic origin (south and north of the country), and iii) a combination of kernel type and geographic origin. The third option was considered the best classification criterion, since it takes into account two points which are closely related to the distribution of diversity: genotypic composition and geographical origin. The following five groups were identified in the collection: a) Pop, b) Floury, e) Dent, d) Southern Flint-semiflints, and e) Northern Flint-semiflints. A total of 90 accessions were selected to constitute the Uruguayan Maize Core Collection. Each group was represented in the Core in proportion to the logarithm of its size. The ranges of 17 variables in the Core were compared with those in the entire collection to verify the representativeness of the subset. On average, 91.2% of the ranges were retained in the Core, confirming its representativeness.